Assessing the Degree of Compliance with the Ethical Principles of the 'Translator’s Professional Guide' amongst Translators in Saudi Arabia - Asiri, Eisa Ahmad S; Bin-Hady, Wagdi; Sahari, Yousef (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
This study assesses the awareness and understanding of the Literature, Publishing and Translation Commission (LPTC) / Saudi Arabian Translation Association (SATA) code of ethics amongst translators in Saudi Arabia, along with their degree of compliance exhibited in their practice with respect to specific ethical principles outlined in the code. Factors that may influence ethical code compliance, such as training, experience and organisational support, are examined. A mixed method approach was adopted for data collection and analysis. A self-built questionnaire comprising 39 items was developed based on the Saudi Translators’ Professional Guide. Interviews were also conducted in order to gather data pertaining to factors that influence Saudi translators’ compliance with the ethics code. The findings indicate that Saudi translators have an extremely high awareness of the LPTC/SATA code (mean score 4.33 ± 0.52), with female translators demonstrating a higher degree of compliance than their male counterparts. The length of professional experience marginally affected translators’ divergence in their ethical code adherence, specifically, within the limits of translator competence. Differences were detected between translators with between 6-10 and 11-15 years, between 6-10 and > 20 years, and between 11-15 and > 20 years of experience. Qualitative findings suggested that the challenges which prevent ethical code compliance include an absence of awareness, a lack of the training and the tools required, an inability to balance professional and ethical requisites, as well as translational task complexity.